Teachers' Perceptions Toward Electronic Student Worksheet Based on Waste Treatment Projects to Improve Students' Creative Thinking Skills - Tisrin Maulina Dewi; Putut Marwoto; Sunyoto Eko Nugroho; Muhiri Muhiri (Yayasan Keluarga Guru Mandiri, 2025)
This research aims to describe the perceptions of SMA/MA science teachers regarding the use of project-based electronic worksheets (e-worksheets) regarding the use of banana peel and chicken eggshell waste to improve students' creative thinking skills. The research method used is a mixed method with Sequential Explanatory Design. Data was collected through a questionnaire and interview and then analyzed using a descriptive approach. Questionnaires were distributed to 20 science teachers, and interviews were conducted with five science teachers. The research results show that teachers positively perceive using project-based e-worksheets to utilize banana peel and chicken eggshell waste. From these results, as many as 65% of teachers have not used project-based e-worksheets. One of the environmental problems faced in Karimun Regency is the abundance of banana peel and chicken eggshell waste, which causes environmental pollution in people's homes. The currently available worksheets do not fully develop students' creative thinking skills, which are low. From the research results, it can be concluded that a project-based e-worksheet for processing banana peel and chicken eggshell waste is necessary to improve students' creative thinking skills as an alternative teaching material in the learning process.